Correlation between fatigue and quality of life among patients with neuromyelitis optica in West China - Miao, Xiaohui; Liu, Qi (Frontiers in Neurology, 2025)
ObjectiveTo investigate the current status and determinants of fatigue and to examine the relationship between fatigue and quality of life (QOL) in patients with neuromyelitis optica (NMO).MethodsEligible patients with NMO were assessed with the Fatigue Impact Scale (FIS) and the Chinese version of the Multiple Sclerosis Quality of Life-54 (MSQOL-54). Clinical factors influencing fatigue were explored and the association between fatigue and QOL was analyzed.ResultsSixty-nine patients (mean age 40.13 years, male/female 6/63) were enrolled. The median Expanded Disability Status Scale (EDSS) score was 3, and 75.4% were seropositive for NMO-IgG. The total FIS score was 67.12 ± 41.24, accounted for by the three sub-dimensions: cognitive fatigue 13.80 ± 9.63, physical fatigue 20.48 ± 12.93, and psychosocial fatigue 32.84 ± 20.94. EDSS scores were positively correlated with total fatigue and all its subdomains; the number of relapses was positively correlated with cognitive fatigue; total fatigue and its subdomains were moderately and negatively correlated with all QOL dimensions.ConclusionDisability status in NMO patients is associated with overall fatigue and its subdomains; relapse frequency is linked to cognitive fatigue; fatigue is negatively correlated with quality of life.